Barriers and facilitators to mental health help-seeking among African American youth and their families: A systematic review study. (June 2019) - Planey, Arrianna M.; Smith, Shardé McNeil; Moore, Stephanie; Walker, Taylor D.
Abstract: It is well documented that African American/Black youth underutilize mental health services. Thus, the aim of this narrative systematic review study was to examine the barriers to, and facilitators of, mental health help-seeking and service utilization for Black youth. The research team conducted a systematic review of qualitative and quantitative studies published from January 2000 to May 2017. Articles were included if they reported (i) barriers and/or facilitators of mental health help-seeking or outpatient mental health service use for Black youth and (ii) non-aggregated findings on African American or Black youth aged 18 and under. Fifteen articles (six quantitative, eight qualitative, and one mixed-method) met the inclusion criteria. Seven themes related to barriers were identified: child-related factors; clinician and therapeutic factors; stigma; religion and spirituality; treatment affordability, availability, and accessibility; the school system; and social network. Seven themes were also identified for facilitators: child mental health concerns; caregivers' experiences; supportive social network; positive therapeutic factors; religion and spirituality; referrals and mandates by parents and gatekeepers; and geographic region. Taken together, the identified barriers to and facilitators of mental health help-seeking among Black youth were multi-scalar (individual-, interpersonal-, and structural-level) and socially-embedded, reflecting help-seeking and service use for Black youth as a complex, contextual, and relational process. Findings support the need for reducing barriers of mental health care access and service use among a population whose need often outstrips actual use of services. Highlights: Among African American youth, need for mental health services outstrips utilization. Facilitators of and barriers to African American youth service use are understudied. Access to mental health services is a relational and socially-embedded process. Studies of mental health service use should assess barriers and facilitators jointly.